Deep ultraviolet vertical structure LED based on porous structure and preparation method thereof
Through the preparation method of deep ultraviolet vertical structure LEDs with porous AlGaN layer formed on a sapphire substrate, the problems of low light extraction efficiency and high dislocation density of AlGaN-based ultraviolet LEDs are solved, and efficient light extraction and performance improvement are achieved.
Patent Information
- Application Number
- CN202411250645.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-20
AI Technical Summary
Due to the low light extraction efficiency and high dislocation density, AlGaN-based ultraviolet LED cannot replace mercury lamps as the new generation of ultraviolet light source. At the same time, there are damage during the stripping process, affecting device performance.
The deep ultraviolet vertical structure LED preparation method with porous structure is grown on the sapphire substrate by metal organic chemical deposition method and electrochemical etching method to form a porous AlGaN layer to reduce dislocation Density and improve light extraction efficiency, and LED preparation of vertical structure is achieved through metal bonding bonding layer and laser peeling process.
It effectively improves the light extraction efficiency and comprehensive performance of deep ultraviolet LEDs, reduces damage during peeling, obtains a high-quality epitaxial layer, and improves the overall performance of the device.
Smart Images

Figure CN119170717A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductor optoelectronic devices, and in particular relates to a deep ultraviolet vertical structure LED based on a porous structure and a preparation method thereof. Background Art
[0002] AlGaN-based UV LEDs have great development prospects in the fields of disinfection and sterilization, UV curing, and biomedicine. At present, AlGaN-based UV LEDs cannot replace mercury lamps as a new generation of UV light sources due to low light extraction efficiency. Due to its unique energy band structure, the prepared LEDs have a lateral mode when emitting light, resulting in low light extraction efficiency on the light output surface; at the same time, the epitaxial wafers prepared by the traditional AlGaN-based deep UV LED epitaxial growth method have a high dislocation density, resulting in low internal quantum efficiency. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide a deep ultraviolet vertical structure LED based on a porous structure and a preparation method thereof in view of the deficiencies in the above-mentioned prior art, so as to solve the technical problems of high light extraction efficiency and dislocation density. At the same time, the porous structure can effectively reduce the damage during the stripping process as a sacrificial layer, thereby improving the device performance.
[0004] The present invention adopts the following technical solutions:
[0005] A method for preparing a deep ultraviolet vertical structure LED based on a porous structure comprises the following steps:
[0006] S1. Growing an AlN buffer layer and an AlGaN pretreatment layer in sequence on a sapphire substrate by metal organic chemical deposition method;
[0007] S2, converting the AlGaN pretreatment layer obtained in step S1 into a porous AlGaN layer by electrochemical etching;
[0008] S3, growing an epitaxial layer on the porous AlGaN layer obtained in step S2 by metal organic chemical deposition method;
[0009] S4, prepare the reflector and P electrode, prepare the metal bonding adhesive layer, wafer bonding, laser lift-off, AlGaN etching, and N electrode evaporation process to obtain a vertical structure LED.
[0010] Specifically, step S1 is as follows:
[0011] TMA, TMG, and NH3 were used as the metal Al source, Ga source, and N source, respectively, and H2 was used as the carrier; the pressure in the reaction chamber was 50 Torr;
[0012] A low-temperature AlN layer with a thickness of 5 to 50 nm is grown at 550 to 650°C;
[0013] A high temperature AlN layer with a thickness of 0.9 to 1.2 μm is grown at 1000 to 1200°C;
[0014] After the AlN buffer layer is obtained, an AlGaN pretreatment layer with a thickness of 1 to 2 μm is grown on the AlN buffer layer at a growth temperature of 1000 to 1200°C.
[0015] Furthermore, the sapphire substrate is pre-treated, specifically:
[0016] The sapphire is placed in a metal organic chemical deposition chamber in a hydrogen atmosphere and heated to 950-1050°C for 10-20 minutes for preheating, and then subjected to a surface nitridation treatment in a mixed gas atmosphere of hydrogen and ammonia for 5-15 minutes. A sapphire substrate with a thickness of 300-500 nm is obtained by double-sided polishing.
[0017] Specifically, in step S2, the diameter of the porous AlGaN layer is 10-100 nm, the depth is 0.3-3 μm, and the duty cycle is 30%-80%.
[0018] Furthermore, the inert electrode in the electrochemical etching is a platinum electrode; the electrolyte is any one of nitric acid, hydrofluoric acid, sulfuric acid, oxalic acid, sodium nitrate and sodium chloride with a concentration of 1 to 20 mol / L, the applied voltage during the etching process is 5.0 to 20.0 V, the etching time is 50 to 500 s, and it is blown dry with nitrogen after the etching is completed.
[0019] Specifically, step S3 is as follows:
[0020] S301, growing an N-type AlGaN layer with a thickness of 1 to 3 μm at 800 to 1100° C., wherein the silicon doping concentration in the N-type AlGaN layer is 5×10 17 cm ~3 ~5×10 19 cm ~3 ;
[0021] S302, growing an AlGaN / AlGaN multi-quantum well light-emitting layer at 800-1100° C. for 5-20 cycles, with a thickness of 100-400 nm;
[0022] S303, growing a P-type AlGaN layer with a thickness of 20 to 100 nm at 800 to 1100° C., wherein the magnesium doping concentration in the P-type AlGaN layer is 5×10 17 cm ~3 ~5×10 19 cm ~3 ;
[0023] S304, growing a P-type GaN electron layer with a thickness of 1 to 2 nm at 800 to 1100° C., wherein the magnesium doping concentration in the P-type GaN layer is 1×10 17 cm ~3 ~1×10 19 cm ~3 .
[0024] Specifically, in step S4, the thickness of the reflector is 1-2 μm, the thickness of the P electrode is 1-10 μm, and the thickness of the N electrode is 1-10 μm.
[0025] Specifically, in step S4, a metal bonding layer is prepared using one or more of gold, gold-tin, gold-indium or palladium-indium materials, and the bonding substrate is any one of Si, SiC, AlSi, Cu, CuWo or CuW alloy, with a thickness of 150 to 500 μm; the bonding temperature is 300 to 500° C., the pressure is 250 to 350 Torr, and the time is 5 to 40 min.
[0026] Specifically, in step S4, the residual AlGaN porous layer is etched by ICP etching process, the etching gas is Cl2 and BCl3, and the N-type AlGaN layer is roughened, and the diameter of the pores after roughening is 10-100nm and the depth is 0.1-0.5μm.
[0027] Another technical solution of the present invention is a deep ultraviolet vertical structure LED based on a porous structure.
[0028] Compared with the prior art, the present invention has at least the following beneficial effects:
[0029] A method for preparing a deep ultraviolet vertical structure LED based on a porous structure. The AlN film obtained by a two-step method effectively alleviates the stress caused by lattice mismatch and provides good nucleation conditions for subsequent AlGaN epitaxial growth; the porous AlGaN layer can effectively reduce the dislocation density of the material, and at the same time, as a sacrificial layer, effectively reduces the damage during laser stripping, thereby improving the light extraction efficiency and comprehensive performance of the deep ultraviolet LED.
[0030] Furthermore, in the two-step growth method of the AlN buffer layer, the low-temperature AlN layer provides good nucleation conditions for the high-temperature AlN layer, reducing the thickness of the AlN closed layer and thus reducing its dislocation density; the AlGaN pretreatment layer provides a platform for the preparation of the porous structure.
[0031] Furthermore, double-sided polishing of sapphire allows the laser to better penetrate it to reach the sacrificial layer, thereby improving the stripping efficiency; pre-treating the sapphire layer creates suitable conditions for epitaxial growth.
[0032] Furthermore, the different sizes and duty cycles of the porous AlGaN layer can make the epitaxial layer grow preferentially laterally, which plays a role in early closure and reducing dislocation density; at the same time, it acts as a sacrificial layer for laser stripping, alleviating the damage to the epitaxial layer caused by the stripping process.
[0033] Furthermore, different concentrations and types of electrolytes, as well as different etching voltages and times in electrochemical etching will form porous structures of different sizes and duty cycles, thereby regulating the growth quality and peeling effect of the epitaxial layer; nitrogen drying after etching is to prevent the etching solution from remaining and affecting the quality of subsequent processes.
[0034] Furthermore, the thickness and doping concentration of the N-type AlGaN layer, the AlGaN / AlGaN multi-quantum well light-emitting layer, the P-type AlGaN layer and the P-type GaN layer are the decisive parameters of the deep ultraviolet LED epitaxial layer.
[0035] Furthermore, the reflector can reflect light to increase the light output; the P and N electrodes form good ohmic contact with the epitaxial layer to ensure the normal operation of the LED.
[0036] Furthermore, the metal bonding adhesive layer not only enables perfect bonding between the bonding epitaxial layer and the bonding material, but also has good electrical and thermal conductivity.
[0037] Furthermore, the etching of the residual AlGaN porous layer after stripping is to eliminate the damaged layer caused by stripping; the etching of the N-type AlGaN layer is to roughen the surface and enhance the light extraction effect.
[0038] In summary, the present invention effectively improves the light extraction efficiency of deep ultraviolet LEDs, while reducing the dislocation density of the material and the damage during the stripping process, so as to obtain a high-quality epitaxial layer. At the same time, the porous structure serves as a sacrificial layer during the stripping process, which together promotes the improvement of the comprehensive performance of deep ultraviolet LEDs.
[0039] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 A schematic diagram of epitaxial growth of a deep ultraviolet LED having a porous structure prepared by the present invention;
[0041] Figure 2 Schematic diagram of the deep ultraviolet vertical structure LED with a porous structure prepared by the present invention. DETAILED DESCRIPTION
[0042] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.
[0044] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0045] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.
[0046] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.
[0047] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6-22" means that all real numbers between "6-22" have been listed in this document, and "6-22" is just an abbreviation of these numerical combinations.
[0048] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.
[0049] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0050] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.
[0051] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.
[0052] See also Figure 1 The present invention provides a method for preparing a deep ultraviolet vertical structure LED based on a porous structure, comprising the following steps:
[0053] S1, sequentially growing an AlN buffer layer and an AlGaN pretreatment layer on a pretreated double-sided polished sapphire substrate by metal organic chemical deposition;
[0054] The specific steps of growing the AlN buffer layer and the AlGaN pretreatment layer are as follows:
[0055] S101, growing a low-temperature AlN layer with a thickness of 5 to 50 nm at 550 to 650° C.;
[0056] S102, growing a high temperature AlN layer with a thickness of 0.9 to 1.2 μm at 1000 to 1200° C.;
[0057] S103, after obtaining the AlN buffer layer, growing an AlGaN pretreatment layer with a thickness of 1 to 2 μm thereon at a growth temperature of 1000 to 1200°C.
[0058] The relevant parameters for preparing epitaxial layers by metal organic chemical deposition are:
[0059] TMA, TMG, and NH3 are used as metal Al source, Ga source, and N source, respectively, and H2 is used as a carrier; the pressure of the reaction chamber is 50 Torr; and the temperature is 550-1200°C.
[0060] The specific preprocessing is:
[0061] The sapphire is placed in a metal organic chemical deposition chamber in a hydrogen atmosphere and heated to 950-1050°C for 10-20 minutes for preheating, and then subjected to surface nitridation treatment in a mixed gas atmosphere of hydrogen and ammonia for 5-15 minutes.
[0062] The sapphire substrate needs to be double-sided polished to a thickness of 300 to 500 nm.
[0063] S2, converting the AlGaN pretreatment layer obtained in step S1 into a porous AlGaN layer by electrochemical etching;
[0064] The inert electrode in the electrochemical etching is a platinum electrode; the electrolyte is any one of nitric acid, hydrofluoric acid, sulfuric acid, oxalic acid, sodium nitrate and sodium chloride, and the concentration of the electrolyte is 1-20 mol / L.
[0065] The applied voltage during the etching process is 5.0-20.0V, the etching time is 50-500s, and the sample needs to be cleaned with deionized water after etching and blown dry with nitrogen. The diameter of the porous AlGaN layer obtained after electrochemical etching is 10-100nm, the depth is 0.3-3μm, and the duty cycle is 30%-80%.
[0066] S3, sequentially growing an N-type AlGaN layer, an AlGaN / AlGaN multi-quantum well active region, a P-type AlGaN layer, and a P-type GaN layer on the porous AlGaN layer obtained in step S2 by using a metal organic chemical deposition method;
[0067] S301, growing an N-type AlGaN layer with a thickness of 1 to 3 μm at a temperature of 800 to 1100° C., wherein the silicon doping concentration in the N-type AlGaN layer is 5×10 17 cm ~3 ~5×10 19 cm ~3 ;
[0068] S302, growing an AlGaN / AlGaN multi-quantum well light-emitting layer at a temperature of 800 to 1100° C. for 5 to 20 cycles, with a thickness of 100 to 400 nm;
[0069] S303, growing a P-type AlGaN layer with a thickness of 20 to 100 nm at a temperature of 800 to 1100° C., wherein the magnesium doping concentration in the P-type AlGaN layer is 5×10 17 cm ~3 ~5×10 19 cm ~3 ;
[0070] S304, growing a P-type GaN electron layer with a thickness of 1 to 2 nm at a temperature of 800 to 1100° C., wherein the magnesium doping concentration in the P-type GaN layer is 1×10 17 cm ~3 ~1×10 19 cm ~3 .
[0071] S4, the preparation of vertical structure LED is completed by preparing reflectors and P electrodes, preparing metal bonding adhesive layers, wafer bonding, laser lift-off, AlGaN etching, and N electrode evaporation process.
[0072] The reflector is made of one or more of nickel, aluminum, and platinum materials, with a thickness of 1 to 2 μm; the P electrode is made of one of nickel aluminum, nickel gold, nickel platinum, titanium aluminum, titanium gold, or titanium platinum materials, with a thickness of 1 to 10 μm.
[0073] The bonding layer is made of one or more materials selected from gold, gold-tin, gold-indium or palladium-indium.
[0074] The bonding substrate is any one of Si, SiC, AlSi, Cu, CuWo or CuW alloy, and has a thickness of 150 to 500 μm.
[0075] The bonding related parameters are:
[0076] The temperature is 300-500°C, the pressure is 250-350 Torr, and the time is 5-40 minutes.
[0077] The laser stripping wavelength is 193nm; after stripping, the residual AlGaN porous layer is etched by ICP etching process, the etching gas is Cl2 and BCl3, and the N-type AlGaN layer is roughened. The diameter of the holes after roughening is 10-100nm and the depth is 0.1-0.5μm.
[0078] The parameters for roughening the N-type AlGaN layer are:
[0079] The concentration of potassium hydroxide solution is 1 to 6 mol / L; the temperature is 80 to 100°C and the etching time is 50 to 70 minutes.
[0080] The N electrode is made of one or more of nickel, titanium, aluminum, gold, platinum, and vanadium, and has a thickness of 1 to 10 μm.
[0081] The present invention discloses a deep ultraviolet vertical structure LED based on a porous structure. Figure 1 From bottom to top in the figure, they are: pre-treated double-polished sapphire substrate, AlN buffer layer grown by two-step method, porous AlGaN layer as sacrificial layer, N-type AlGaN layer, AlGaN / AlGaN multi-quantum well light-emitting layer, P-type AlGaN layer and P-type GaN layer.
[0082] See also Figure 2 , from bottom to top in the figure are: CuW substrate, Ti / Au / AuSn bonding layer, Ti / Al reflector and ohmic contact layer, P-type GaN layer, P-type AlGaN layer, AlGaN / AlGaN multi-quantum well light-emitting layer, N-type AlGaN layer and N electrode.
[0083] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0084] Example 1
[0085] Take a 300μm thick double-sided polished sapphire substrate, clean it and put it into a metal organic chemical vapor deposition (MOCVD) device, use TMA, TMG, NH3 as metal Al source, Ga source, N source, and H2 as carrier; the reaction chamber pressure is 50Torr; the temperature is 550℃;
[0086] The sapphire substrate is pretreated by placing it in a metal organic chemical deposition chamber with a hydrogen atmosphere before growth, and heated to 1000°C for 15 minutes for preheating, and then subjected to surface nitridation treatment in a mixed gas atmosphere of hydrogen and ammonia for 10 minutes;
[0087] After pretreatment, the temperature was lowered to 580°C, and a 6nm thick low-temperature AlN layer was grown on a double-sided polished sapphire substrate;
[0088] The temperature is raised to 1000°C, and a high-temperature AlN layer with a thickness of 1 μm is grown;
[0089] After obtaining the AlN buffer layer, an AlGaN pretreatment layer with a thickness of 1 μm is grown thereon;
[0090] The obtained sample was then divided into equal parts, connected to the positive pole of a DC power supply as an anode, and the platinum electrode was connected to the negative pole of a DC power supply as a cathode, and placed in a 10 mol / L nitric acid electrolyte.
[0091] The applied etching voltage was set to 5 V, 10 V, and 15 V, and electrochemical etching was performed for 200 s.
[0092] After etching, the samples were rinsed with deionized water and dried with nitrogen.
[0093] AlGaN porous layers with three pore sizes can be obtained by applying different external voltages.
[0094] The etched sample is then placed in a metal organic chemical vapor deposition (MOCVD) device to sequentially grow an N-type AlGaN layer, an AlGaN / AlGaN multi-quantum well active region, a P-type AlGaN layer, and a P-type GaN layer.
[0095] After the epitaxial layer growth is completed, the reflective layer (Ni / Al / Pt) and the P electrode, that is, the TI / Al layer with a thickness of 1 μm, are prepared by an evaporation process.
[0096] After the above-mentioned evaporation process is completed, the Ti / Au / AuSn layer is continuously evaporated as a metal bonding adhesive layer, and AuSn should be evaporated on the 150 μm CuW alloy substrate to be bonded.
[0097] Then, the epitaxial layer with the metal vaporized thereon and the substrate layer to be bonded are brought into contact with each other and placed in a bonding machine for wafer bonding at a temperature of 300°C and an applied pressure of 350 Torr for 10 minutes.
[0098] After wafer bonding, the sapphire substrate is peeled off through the laser lift-off process;
[0099] After the laser lift-off process is completed, the residual AlGaN porous layer is plasma etched using an ICP etching process, with the etching gases being Cl2 and BCl3;
[0100] The sample was then placed in a beaker containing 2 mol / L potassium hydroxide solution and placed on a heating table, and etched at 80° C. for 60 minutes to complete the roughening of the N-type AlGaN.
[0101] After etching, an N electrode is evaporated with a thickness of 2 μm to complete the preparation of the vertical structure.
[0102] By preparing a porous AlGaN substrate, the embedded porous structure can improve the longitudinal dislocation problem during its growth, thereby improving the internal quantum efficiency of luminescence.
[0103] Example 2
[0104] Take a 500μm thick double-sided polished sapphire substrate, clean it and put it into a metal organic chemical vapor deposition (MOCVD) device, use TMA, TMG, NH3 as metal Al source, Ga source, N source, and H2 as carrier; the reaction chamber pressure is 50Torr; the temperature is 1200℃;
[0105] The sapphire substrate is pretreated by placing it in a metal organic chemical deposition chamber with a hydrogen atmosphere before growth, and heated to 950°C for 20 minutes for preheating, and then subjected to surface nitridation treatment in a mixed gas atmosphere of hydrogen and ammonia for 15 minutes;
[0106] After pretreatment, the temperature was lowered to 600°C, and a 10nm thick low-temperature AlN layer was grown on a double-sided polished sapphire substrate;
[0107] The temperature was raised to 1100°C, and a high-temperature AlN layer with a thickness of 1.1 μm was grown;
[0108] After obtaining the AlN buffer layer, an AlGaN pretreatment layer with a thickness of 2 μm is grown thereon;
[0109] The obtained sample was then divided into equal parts, connected to the positive electrode of a DC power supply as an anode, and the platinum electrode was connected to the negative electrode of a DC power supply as a cathode, and placed in a 5 mol / L nitric acid electrolyte.
[0110] The applied etching voltage was set to 10 V, and the electrochemical etching was performed on the equal-divided samples for 100 s, 200 s, and 300 s, respectively.
[0111] After etching, the samples were rinsed with deionized water and dried with nitrogen.
[0112] AlGaN porous layers with three pore sizes can be obtained by different etching times.
[0113] The etched sample is then placed in a metal organic chemical vapor deposition (MOCVD) device to sequentially grow an N-type AlGaN layer, an AlGaN / AlGaN multi-quantum well active region, a P-type AlGaN layer, and a P-type GaN layer.
[0114] After the epitaxial layer growth is completed, the reflective layer (Ni / Al / Pt) and the P electrode, that is, the TI / Al layer with a thickness of 1 μm, are prepared by an evaporation process.
[0115] After the above-mentioned evaporation process is completed, the Ti / Au / AuSn layer is continuously evaporated as a metal bonding adhesive layer, and AuSn is evaporated on the 250 μm CuW alloy substrate to be bonded.
[0116] Then, the epitaxial layer with metal vaporized thereon and the substrate layer to be bonded are contacted with each other and placed in a bonding machine for wafer bonding at a temperature of 500°C and an applied pressure of 250 Torr for 15 minutes.
[0117] After wafer bonding, the sapphire substrate is peeled off through the laser lift-off process;
[0118] After the laser lift-off process is completed, the residual AlGaN porous layer is plasma etched using an ICP etching process, with the etching gases being Cl2 and BCl3;
[0119] The sample was then placed in a beaker containing 3 mol / L potassium hydroxide solution and placed on a heating table, and etched at 90° C. for 70 minutes to complete the roughening of the N-type AlGaN.
[0120] After etching, an N electrode is evaporated with a thickness of 2 μm to complete the preparation of the vertical structure.
[0121] Example 3
[0122] Take a 400μm thick double-sided polished sapphire substrate, clean it and put it into a metal organic chemical vapor deposition (MOCVD) device, use TMA, TMG, NH3 as metal Al source, Ga source, N source, and H2 as carrier; the reaction chamber pressure is 50Torr; the temperature is 850℃;
[0123] The sapphire substrate is pretreated by placing it in a metal organic chemical deposition chamber with a hydrogen atmosphere before growth, and heated to 1050°C for 10 minutes for preheating, and then subjected to surface nitridation treatment in a mixed gas atmosphere of hydrogen and ammonia for 5 minutes;
[0124] After pretreatment, the temperature was lowered to 650°C, and a 20nm thick low-temperature AlN layer was grown on a double-sided polished sapphire substrate;
[0125] The temperature was raised to 1200°C, and a high-temperature AlN layer with a thickness of 1.2 μm was grown;
[0126] After obtaining the AlN buffer layer, an AlGaN pretreatment layer with a thickness of 3 μm is grown thereon;
[0127] The obtained sample is chemically etched to transform the AlGaN layer into a porous layer. The specific operation is as follows:
[0128] Place a beaker containing 1 mol / L potassium hydroxide solution on a heating table, heat it to 90°C, and etch the sample in the potassium hydroxide solution for 60 minutes;
[0129] After etching, the samples were rinsed with deionized water and then dried with nitrogen.
[0130] The etched sample is then placed in a metal organic chemical vapor deposition (MOCVD) device to sequentially grow an N-type AlGaN layer, an AlGaN / AlGaN multi-quantum well active region, a P-type AlGaN layer, and a P-type GaN layer.
[0131] After the epitaxial layer growth is completed, the reflective layer (Ni / Al / Pt) and the P electrode, that is, the TI / Al layer with a thickness of 1 μm, are prepared by an evaporation process.
[0132] After the above-mentioned evaporation process is completed, the Ti / Au / AuSn layer is continuously evaporated as a metal bonding adhesive layer, and AuSn is simultaneously evaporated on the 200 μm CuW alloy substrate to be bonded.
[0133] Then, the epitaxial layer with metal vaporized thereon and the layer of the substrate to be bonded are brought into contact with each other and placed in a bonding machine for wafer bonding at a temperature of 400° C. and an applied pressure of 300 Torr for 30 minutes.
[0134] After wafer bonding, the sapphire substrate is peeled off through the laser lift-off process.
[0135] After the laser lift-off process is completed, the residual AlGaN porous layer is plasma etched using an ICP etching process, with the etching gases being Cl2 and BCl3;
[0136] The sample was then placed in a beaker containing 5 mol / L potassium hydroxide solution, placed on a heating table, and etched at 100° C. for 50 minutes to complete the roughening of the N-type AlGaN.
[0137] After etching, an N electrode is evaporated with a thickness of 2 μm to complete the preparation of the vertical structure.
[0138] Example 4
[0139] Take a 400μm thick double-sided polished sapphire substrate, clean it and put it into a metal organic chemical vapor deposition (MOCVD) device, use TMA, TMG, NH3 as metal Al source, Ga source, N source, and H2 as carrier; the reaction chamber pressure is 50Torr; the temperature is 850℃;
[0140] The sapphire substrate is pretreated by placing it in a metal organic chemical deposition chamber with a hydrogen atmosphere before growth, and heated to 1050°C for 10 minutes for preheating, and then subjected to surface nitridation treatment in a mixed gas atmosphere of hydrogen and ammonia for 5 minutes;
[0141] After pretreatment, the temperature was lowered to 650°C, and a 20nm thick low-temperature AlN layer was grown on a double-sided polished sapphire substrate;
[0142] The temperature was raised to 1200°C, and a high-temperature AlN layer with a thickness of 1.2 μm was grown;
[0143] After obtaining the AlN buffer layer, an AlGaN pretreatment layer with a thickness of 3 μm is grown thereon;
[0144] After etching, the samples were rinsed with deionized water and then dried with nitrogen.
[0145] The etched sample is then placed in a metal organic chemical vapor deposition (MOCVD) device to sequentially grow an N-type AlGaN layer, an AlGaN / AlGaN multi-quantum well active region, a P-type AlGaN layer, and a P-type GaN layer.
[0146] After the epitaxial layer growth is completed, the reflective layer (Ni / Al / Pt) and the P electrode, that is, the TI / Al layer with a thickness of 1 μm, are prepared by an evaporation process.
[0147] After the above-mentioned evaporation process is completed, the Ti / Au / AuSn layer is continuously evaporated as a metal bonding adhesive layer, and AuSn is simultaneously evaporated on the 200 μm CuW alloy substrate to be bonded.
[0148] Then, the epitaxial layer with metal vaporized thereon and the layer of the substrate to be bonded are brought into contact with each other and placed in a bonding machine for wafer bonding at a temperature of 400° C. and an applied pressure of 300 Torr for 30 minutes.
[0149] After wafer bonding, the sapphire substrate is peeled off by laser lift-off process. The obtained sample is chemically etched to transform the AlGaN layer into a porous layer. The specific operation is as follows:
[0150] A beaker containing 1 mol / L potassium hydroxide solution was placed on a heating table and heated to 90°C. The sample was placed in the potassium hydroxide solution and etched for 60 minutes. After etching, an N electrode was evaporated through photolithography and ICP process with an electrode thickness of 2 μm to complete the preparation of the vertical structure.
[0151] This structure can effectively improve the light extraction problem of deep ultraviolet LEDs.
[0152] To sum up, the present invention provides a deep ultraviolet vertical structure LED based on a porous structure and a preparation method thereof. The porous structure and the deep ultraviolet vertical structure process are prepared by an electrochemical process, which can effectively improve the quality of deep ultraviolet epitaxial growth. The porous structure can also effectively enhance the light extraction efficiency of the deep ultraviolet light source.
[0153] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a deep ultraviolet vertical structure LED based on a porous structure. It is characterized in that The following steps are involved: S1. Growing an AlN buffer layer and an AlGaN pretreatment layer in sequence on a sapphire substrate by metal organic chemical deposition method; S2, converting the AlGaN pretreatment layer obtained in step S1 into a porous AlGaN layer by electrochemical etching; S3, growing an epitaxial layer on the porous AlGaN layer obtained in step S2 by metal organic chemical deposition method; S4, prepare the reflector and P electrode, prepare the metal bonding adhesive layer, wafer bonding, laser lift-off, AlGaN etching, and N electrode evaporation process to obtain a vertical structure LED.
2. The method for preparing a deep ultraviolet vertical structure LED based on a porous structure according to claim 1, It is characterized in that Step S1 is specifically as follows: TMA, TMG, NH 3 As a metal source of Al, Ga, and N, H 2 is the carrier; the reaction chamber pressure is 50Torr; A low-temperature AlN layer with a thickness of 5 to 50 nm is grown at 550 to 650°C; A high temperature AlN layer with a thickness of 0.9 to 1.2 μm is grown at 1000 to 1200°C; After the AlN buffer layer is obtained, an AlGaN pretreatment layer with a thickness of 1 to 2 μm is grown on the AlN buffer layer at a growth temperature of 1000 to 1200°C.
3. The method for preparing a deep ultraviolet vertical structure LED based on a porous structure according to claim 2, It is characterized in that First, pre-treat the sapphire substrate, specifically: The sapphire is placed in a metal organic chemical deposition chamber in a hydrogen atmosphere and heated to 950-1050°C for 10-20 minutes for preheating, and then surface nitridation treatment is performed in a mixed gas atmosphere of hydrogen and ammonia for 5-15 minutes. After double-sided polishing, a sapphire substrate with a thickness of 300-500 μm is obtained.
4. The method for preparing a deep ultraviolet vertical structure LED based on a porous structure according to claim 1, It is characterized in that In step S2, the diameter of the porous AlGaN layer is 10-100 nm, the depth is 0.3-3 μm, and the duty cycle is 30%-80%.
5. The method for preparing a deep ultraviolet vertical structure LED based on a porous structure according to claim 4, It is characterized in that The inert electrode in the electrochemical etching is a platinum electrode; the electrolyte is any one of nitric acid, hydrofluoric acid, sulfuric acid, oxalic acid, sodium nitrate and sodium chloride with a concentration of 1 to 20 mol / L; the applied voltage during the etching process is 5.0 to 20.0 V; the etching time is 50 to 500 s; and the etching is dried with nitrogen after completion.
6. The method for preparing a deep ultraviolet vertical structure LED based on a porous structure according to claim 1, It is characterized in that Step S3 is specifically as follows: S301, growing an N-type AlGaN layer with a thickness of 1 to 3 μm at 800 to 1100° C., wherein the silicon doping concentration in the N-type AlGaN layer is 5×10 17 cm ~3 ~5×10 19 cm ~3 ; S302, growing an AlGaN / AlGaN multi-quantum well light-emitting layer at 800-1100° C. for 5-20 cycles, with a thickness of 100-400 nm; S303, growing a P-type AlGaN layer with a thickness of 20 to 100 nm at 800 to 1100° C., wherein the magnesium doping concentration in the P-type AlGaN layer is 5×10 17 cm ~3 ~5×10 19 cm ~3 ; S304, growing a P-type GaN electron layer with a thickness of 1 to 2 nm at 800 to 1100° C., wherein the magnesium doping concentration in the P-type GaN layer is 1×10 17 cm ~3 ~1×10 19 cm ~3 .
7. The method for preparing a deep ultraviolet vertical structure LED based on a porous structure according to claim 1, It is characterized in that In step S4, the thickness of the reflector is 1-2 μm, the thickness of the P electrode is 1-10 μm, and the thickness of the N electrode is 1-10 μm.
8. The method for preparing a deep ultraviolet vertical structure LED based on a porous structure according to claim 1, It is characterized in that In step S4, a metal bonding layer is prepared using one or more of gold, gold-tin, gold-indium or palladium-indium materials, and the bonding substrate is any one of Si, SiC, AlSi, Cu, CuWo or CuW alloy, with a thickness of 150 to 500 μm; the bonding temperature is 300 to 500° C., the pressure is 250 to 350 Torr, and the time is 5 to 40 min.
9. The method for preparing a deep ultraviolet vertical structure LED based on a porous structure according to claim 1, It is characterized in that In step S4, the residual AlGaN porous layer is etched by ICP etching process, and the etching gas is Cl 2 and BCl 3 , and the N-type AlGaN layer is roughened, and the diameter of the holes after roughening is 10 to 100 nm and the depth is 0.1 to 0.5 μm.
10. A deep ultraviolet vertical structure LED based on a porous structure, It is characterized in that It is prepared according to the method for preparing a deep ultraviolet vertical structure LED based on a porous structure according to any one of claims 1 to 9.
